2003
DOI: 10.1109/titb.2003.808512
|View full text |Cite
|
Sign up to set email alerts
|

A single mediaprocessor-based programmable ultrasound system

Abstract: We have developed a programmable ultrasound imaging system using a single commercially available mediaprocessor. We have efficiently mapped all of the necessary B-mode processing algorithms on the underlying processor architecture, including envelope detection, dynamic range compression, lateral and axial filtering, persistence processing, and scan conversion. Our system can handle varying specifications ranging from 128 vectors and 512 samples per vector to more than 256 vectors and 1024 samples per vector. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Computing platforms, such as field-programmable gate array (FPGA), digital signal processor (DSP) and media processors, have capabilities in terms of hardware to realize complex ultrasound signal processing algorithms in real time. In [3], ultrasound signal processing is performed on a single media processor; due to the computational limitations of the processor, the beamformed data are acquired through an ultrasound research interface from a high-end system, and the real-time mid-end and back-end processing algorithms are implemented on a media processor. In [4], a complete standalone ultrasound scanning machine is realized using single FPGA and a proposed pseudo-dynamic received beamforming with an extended aperture technique targeting the PUS system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computing platforms, such as field-programmable gate array (FPGA), digital signal processor (DSP) and media processors, have capabilities in terms of hardware to realize complex ultrasound signal processing algorithms in real time. In [3], ultrasound signal processing is performed on a single media processor; due to the computational limitations of the processor, the beamformed data are acquired through an ultrasound research interface from a high-end system, and the real-time mid-end and back-end processing algorithms are implemented on a media processor. In [4], a complete standalone ultrasound scanning machine is realized using single FPGA and a proposed pseudo-dynamic received beamforming with an extended aperture technique targeting the PUS system.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, portable ultrasound scanning machines are realized on FPGAs, DSPs and media processors [2][3][4], and the automatic detection of kidneys in CT images based on random forest is proposed. The algorithms proposed for CT images will not work for ultrasound images, as the characteristics of kidney change with imaging modality, and the kidney images acquired through ultrasound scanning depend on the person who scans.…”
Section: Introductionmentioning
confidence: 99%
“…Since a conventional medical ultrasound imaging system requires a plenty of computational complexity, an ultrasound imaging system has been traditionally realized with a dedicated hardware architecture utilizing application-specific integrated circuits (ASICs) or field-programmable gate array (FPGA) chips [1]. By virtue of the improvement in programmable processors, various software-based architectures for medical ultrasound imaging systems were proposed in the past decades [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of the improvement in programmable processors, various software-based architectures for medical ultrasound imaging systems were proposed in the past decades [2,3]. However, for the beamformer, hybrid architecture based on combination of digital signal processors (DSPs) and ASICs/FPGA was applied in developing a commercial ultrasound machine because it demands intensive computational power [4].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, by utilizing recent advances in digital signal processors (DSPs), we have demonstrated the advantages of programmable architectures for back-end processing. For example, it was found that programmable architectures enable the system to be updated and new applications to be introduced in software rather than hardware [1], leading to higher flexibility and reduced time-to-market and development costs. However, ASICs were still used in many ultrasound systems to support the more-challenging frontend processing.…”
Section: Introductionmentioning
confidence: 99%